A Review of Ayurvedic Approach in Convalescent Care. - Aabha , Shankar K; Shobhana, M C (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Most of the diseases come up or get worsened with the results of staggering health condition of its survivors. It was happened in case of Covid pandemic too. It definitely had a deleterious impact on human health and economy. This certainly hint towards the need to implement a health promotion strategy during the period of convalescence. Convalescence is the period of recuperation of health after a serious illness or injury or weakness. The care given during this period are meant to improve immunity, body strength and vitality in a systematic manner by providing gradual nourishment and also to prevent further occurrence of the disease. Materials And Methods: A comprehensive literature search related to convalescent care and description related to basic principles of Ayurveda using all available Ayurvedic compendium, research papers, editorials and review papers from various databases were thoroughly screened, compiled, analyzed and presented in a systematic manner. Results And Discussion: Health is depended up on Bala. Convalescent care in Ayurveda comprises the practices that enhance Bala and Vyadhikshamatva and improve the quality of life after an illness/weakness, gradually bringing back to normalcy. In Ayurveda, the intention of convalescent care is to bring back Dhatusamya which was deranged by a disease or due to intense treatment Bheshajakshapita. Such a care is essential during some physiological conditions like Garbha kaala and Soothika kaala also.